Youth with disabilities are more likely than their peers to engage in hazardous child labour. (4th November 2020) - Emerson, Eric; Llewellyn, Gwynnyth
Abstract: Background: Little is known about the extent to which children and adolescents with disabilities are exposed to child labour. Objective: To estimate prevalence rates and adjusted rate ratios of exposure to child labour among children and adolescents with/without disability in middle‐ and low‐income countries and to determine whether these rates vary between functional limitations associated with disability. Participants and Setting: Nationally representative samples involving 142, 499 children aged 5–14 from 15 countries. Methods: Secondary analysis of data collected in UNICEF's Multiple Indicator Cluster Surveys. Results: Overall children and youth with disability were not at significantly greater risk of exposure than children without disability to child labour when demographic and contextual factors were taken into account. However, children and youth with disability were at significantly greater risk of exposure than children without disability to hazardous child labour (adjusted relative risk [ARR] = 1.15 [1.10–1.21], P < 0.001). Specifically, children and youth with impairments related to poorer mental health or cognitive functioning were at significantly greater risk of exposure to hazardous child labour (e.g., ARR for learning impairment = 1.27 [1.14–1.42], P < 0.001). In contrast, children with impairments related to sensory functioning, mobility and expressive communication were at no greater risk of exposure than children with no disability. Conclusions: Children and youth with disability are at greater risk of exposure to hazardous child labour than children with no disability in middle‐ and low‐income countries. Responses to eradicate hazardous child labour need to take account of the situation of children and youth with disability.